A degradable blister box and preparation method thereof

By using polylactic acid and inorganic fillers in the degradable plastic box and adding antioxidants and other components, through high-temperature smelting and vacuum suction processes, the problem of water absorption and softening and insufficient mechanical strength of the plastic box under high temperature conditions is solved, and the problem of water absorption and softening of the plastic box under high temperature conditions is achieved. A blister box with high temperature resistance and high strength.

CN116144151BActive Publication Date: 2025-02-18DONGGUAN HANGLE ENVIRONMENTAL PROTECTION PACKAGING MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310036055.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-07
Publication Date
2025-02-18
Estimated Expiration
2043-01-07

AI Technical Summary

Technical Problem

The degradable plastic box on the market is easy to absorb water and soften when it is filled with high-temperature soup or hot drinks. It has insufficient mechanical strength and is very easy to squeeze and deform during transportation, resulting in food spilling out.

Method used

Polylactic acid is used as the main material, and inorganic fillers such as glass fiber, diatomaceous earth and cross-linked microporous starch are added, combined with antioxidants, chain extenders and hydrolyzers, and high temperature resistance is prepared through high-temperature smelting and vacuum suction. , high-strength biodegradable plastic box.

Benefits of technology

It improves the heat resistance, mechanical strength, waterproof and oil-proof properties of the blister box, solves the problems of water absorption and softening and insufficient mechanical strength, ensures that it is not easy to squeeze and deform during transportation, and prevents food from spilling out.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004042669130000041
    Figure BDA0004042669130000041
  • Figure BDA0004042669130000052
    Figure BDA0004042669130000052
  • Figure BDA0004042669130000061
    Figure BDA0004042669130000061
Patent Text Reader

Abstract

The present application relates to the technical field of food packaging materials, and more specifically, it relates to a degradable blister box and a preparation method thereof, comprising the following raw materials: polylactic acid, inorganic filler, antioxidant, chain extender, and hydrolysis resistance agent, wherein the inorganic filler comprises the following raw materials: glass fiber, diatomaceous earth, and cross-linked microporous starch, and the preparation method thereof is as follows: the raw materials are added into a rubber mixer for mixing to obtain a mixture, the mixture is extruded to obtain a sheet, the sheet is heated at a high temperature and then formed by a vacuum suction method, and the sheet is cooled and cut to obtain a degradable blister box, and the prepared blister box has excellent degradability, good heat resistance, and high mechanical strength, is not easy to soften when containing high-temperature soup or hot drinks, and is not easy to be squeezed and deformed during transportation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of food packaging materials, and more specifically, to a degradable blister box and a preparation method thereof. Background Art

[0002] Blister boxes are plastic products produced by the blister process. They are widely used in life and production. They have the advantages of light weight, convenient transportation and good sealing performance. However, the frequent use of blister boxes will generate a lot of garbage, causing environmental pollution. The degradable blister boxes on the market are made of natural materials such as paper products, straw, starch, etc. Although they can be naturally degraded after being discarded and there is no environmental pollution problem, if they are used to hold high-temperature soups or hot drinks, they are easy to absorb water and soften, and the mechanical strength is not enough. They are very easy to be squeezed and deformed during transportation, causing food to spill. Summary of the invention

[0003] In order to solve the problem that the degradable blister boxes on the market used to hold high-temperature soups or hot drinks easily absorb water and soften and have insufficient mechanical strength, and are easily squeezed and deformed during transportation, resulting in food spilling, the present application provides a degradable blister box and a preparation method thereof.

[0004] In the first aspect, the present application provides a biodegradable blister box, which adopts the following technical solution:

[0005] A degradable blister box comprises the following raw materials in parts by weight: 10-60 parts of polylactic acid, 5-30 parts of inorganic filler, 2-10 parts of antioxidant, 1-8 parts of chain extender, and 3-9 parts of hydrolysis resistant agent. The inorganic filler comprises the following raw materials in parts by weight: 1-8 parts of glass fiber, 1-10 parts of diatomaceous earth, and 3-12 parts of cross-linked microporous starch.

[0006] By adopting the above technical scheme, polylactic acid has good biodegradability and can be completely degraded by microorganisms in nature, and finally generates carbon dioxide and water, which makes the blister box more environmentally friendly. In addition, polylactic acid has good heat resistance and solvent resistance, and can be processed by extrusion, biaxial stretching, injection blow molding and the like, so that the blister box has good heat resistance and is convenient to process. By adding inorganic fillers, the heat resistance, strength and wear resistance of the blister box can be further increased. Glass fiber has good heat resistance and high mechanical strength. Diatomaceous earth has a microporous structure, a low density and a large specific surface area. Cross-linked microporous starch has a certain pore structure and is resistant to high temperature. The combination of the three can effectively improve the heat resistance and strength of the blister box. The antioxidant can effectively extend the service life of the blister box, and the chain extender can improve the tensile strength of the blister box. The polylactic acid will disintegrate from the inside during use, which will affect the performance of the blister box. The addition of a hydrolysis-resistant agent can effectively prevent the progress of this process and maintain the excellent performance of the blister box.

[0007] Preferably, the polylactic acid is a mixture of left-handed polylactic acid and right-handed polylactic acid, and the mixing ratio of the left-handed polylactic acid to the right-handed polylactic acid is (6-9):1.

[0008] By adopting the above technical solution and after many experiments by the inventors, it was found that the heat resistance, strength and plasticity of L-polylactic acid and D-polylactic acid can be further improved by compounding them in a certain proportion.

[0009] Preferably, the cross-linked microporous starch is prepared by the following steps:

[0010] Step (1): 20-50 parts of corn starch are ball-milled and mixed with 30-60 parts of water, added into a reaction container, stirred, and preheated at 10-45° C. for 20-30 minutes, and then 1-2.5 parts of sodium chloride solution and 2-8 parts of epichlorohydrin are slowly added to obtain a starch emulsion, and then 3-4 parts of 1 mol / L sodium hydroxide solution are added, reacted for 4 hours, and then 2-5 parts of 1 mol / L hydrochloric acid are added, and the mixture is filtered, washed, dried, and crushed to obtain a cross-linked starch;

[0011] Step (2): adding water to the cross-linked starch obtained in step (1) to prepare a solution with a mass concentration of 20-30%, then adding 10-15 parts of phosphate buffer, heating in a water bath at 60-65° C. and stirring for 20-50 minutes to obtain a mixed emulsion;

[0012] Step (3): dissolving 2-5 parts of the complex enzyme with 5-10 parts of phosphate buffer to form an enzyme solution, and then slowly adding it to the mixed emulsion. After reacting for 5-10 hours, centrifuging, washing the obtained solid with water and drying, the cross-linked microporous starch can be obtained.

[0013] By adopting the above technical scheme, a cross-linked microporous starch with a pore structure, high heat resistance and good adsorption can be prepared. After ball milling, the pore depth and pore diameter of corn starch can be increased, and its adsorption performance can be increased. Water is used to disperse corn starch. The purpose of preheating treatment is to weaken the hydrogen bond strength of starch molecules. The sodium chloride solution increases the gelatinization temperature of corn starch, so that corn starch is not easy to gelatinize when heated, and the reaction effect between starch molecules and epichlorohydrin is reduced. Epichlorohydrin cross-links starch molecules in an alkaline medium to form a spatial network structure, thereby improving the acid resistance, alkali resistance, viscosity and heat resistance of corn starch. The invention relates to a method for preparing a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack. The blister pack is used to prepare a blister pack.

[0014] Preferably, the composite enzyme is a composite of saccharifying enzyme and α-amylase in a mass ratio of (2-3):1.

[0015] By adopting the above technical scheme, according to the inventor's multiple experiments, saccharifying enzyme and α-amylase are used in a compound ratio of (2-3):1 by mass, and the obtained cross-linked microporous starch has a higher degree of hydrolysis, a better honeycomb pore structure, and better heat resistance.

[0016] In a second aspect, the present application provides a method for preparing a degradable blister box, using the following technical solution:

[0017] A method for preparing a degradable blister box comprises the following steps:

[0018] Step A: adding 10-60 parts of polylactic acid, 5-30 parts of inorganic filler, 2-10 parts of antioxidant, 1-8 parts of chain extender and 3-9 parts of hydrolysis resistance agent into a rubber mixer for mixing to obtain a mixture;

[0019] Step B: Extruding the mixture obtained in step A to obtain a sheet;

[0020] Step C: The sheet obtained in step B is heated at high temperature and then formed by vacuum suction, and then cooled and cut to obtain a degradable blister box.

[0021] By adopting the above technical scheme, a blister box with high temperature resistance, high strength, water resistance and oil resistance is prepared; the antioxidant, chain extender and hydrolysis resistance react with polylactic acid during the high-temperature melting process to improve the antioxidant capacity, strength and processability of polylactic acid, and the inorganic filler and polylactic acid are evenly mixed so that the prepared blister box has the characteristics of inorganic filler, good heat resistance and high mechanical strength, which solves the problem that high-temperature soup or hot drink is easy to absorb water and soften, and the mechanical strength is not enough and it is very easy to be squeezed and deformed during transportation, resulting in food spilling; after high-temperature heating, it is convenient to shape the sheet material, and the vacuum suction method is simple and efficient, and it is conducive to removing the excess part of the blister box semi-finished product through cutting, so as to obtain a more beautiful and practical blister box.

[0022] Preferably, the mixing temperature in step A is 190° C.-200° C., the stirring speed of the rubber mixer is 40-60 r / min, and the mixing time is 20-30 min.

[0023] By adopting the above technical scheme, when the temperature is lower than 190°C, the polylactic acid is not in a completely molten state, the reaction is difficult to proceed, and it is easy to cause uneven mixing. If the temperature is too high, it is easy to destroy the structure of the raw materials. The melting temperature is preferably 190-200°C, the stirring speed of the rubber mixer is 40-60r / min, and the mixing time is 20-30min, which is sufficient to mix the raw materials of each weight portion evenly.

[0024] Preferably, the heating temperature of the sheet in step C is 150°C-170°C.

[0025] By adopting the above technical solution, if the sheet is heated below 150°C, the sheet cannot soften and it is difficult to shape it by vacuum suction. If the temperature is higher than 170°C, the sheet will soften excessively, which will cause the sheet to shrink and bend, which is not conducive to shaping. The optimal heating temperature is 150-170°C.

[0026] Preferably, the chain extender is sorbitol, polyhydroxyalkanoate or a combination of both.

[0027] By adopting the above technical scheme, sorbitol and polyhydroxyalkanoates can react with the functional groups on the polylactic acid molecular chain to expand the molecular chain and increase the molecular weight, thereby increasing the tensile strength and high temperature resistance of polylactic acid. Sorbitol and polyhydroxyalkanoates can be degraded in nature, thereby improving the degradability of the blister box.

[0028] Preferably, the antioxidant is a combination of phosphite and thiobisphenol.

[0029] By adopting the above technical solution, thiobisphenol is the main antioxidant, phosphite is the auxiliary antioxidant, and the main antioxidant and the auxiliary antioxidant are compounded to achieve a better antioxidant effect, so that the blister box has good anti-aging properties.

[0030] Preferably, the anti-hydrolysis agent is one or a combination of polycarbodiimide and carbodiimide.

[0031] By adopting the above technical scheme, polycarbodiimide and carbodiimide are easy to react with the carboxyl end groups of polylactic acid, thereby reducing the initial mass molar concentration of the carboxyl end groups, and at the same time continuously consuming the carboxyl end groups continuously generated during the hydrolysis of polylactic acid, reducing the catalysis of the carboxyl end groups on the hydrolysis reaction of polylactic acid, and improving the hydrolysis resistance of polylactic acid. Polycarbodiimide is better than carbodiimide, and carbodiimide is cheaper. The combined use of the two can make the hydrolysis resistance of polylactic acid reach a better value and save production costs.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. Polylactic acid has good biodegradability, heat resistance, solvent resistance, easy processing and other properties, which makes the preparation process of blister boxes simple. The prepared blister boxes have a certain heat resistance and can be degraded by microorganisms, which is beneficial to environmental protection; glass fiber has good heat resistance and high mechanical strength, diatomaceous earth has a microporous structure, low density, and large specific surface area, and cross-linked microporous starch has a certain pore structure and high temperature resistance. The three are added to polylactic acid in the form of fillers to effectively improve the heat resistance and mechanical strength of the blister box.

[0034] 2. By adding antioxidants, chain extenders, polyhydrolysis agents to react with polylactic acid, the aging resistance, tensile strength and thermal stability of the blister box can be further increased.

[0035] 3. The raw materials are mixed evenly by high-temperature melting and high-temperature stirring, and the raw materials are fully contacted to make the reaction thorough. The prepared blister box has good heat resistance and high strength. The raw materials are extruded into sheets and shaped by vacuum suction. The process is simple and the production efficiency is fast. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0037] Table 1 Raw material model manufacturer

[0038]

[0039]

[0040] Preparation Example

[0041] Preparation example of cross-linked micropores

[0042] Preparation Example 1

[0043] The cross-linked microporous starch is prepared by the following steps:

[0044] Step (1): 2 kg of corn starch is ball-milled and mixed with 3 kg of water, added to a reaction container, stirred, and preheated at 40° C. for 20 min, and then 0.1 kg of sodium chloride solution and 0.2 kg of epichlorohydrin are slowly added to obtain a starch emulsion, and then 0.3 kg of 1 mol / L sodium hydroxide solution is added. After reacting for 3 hours, 0.2 kg of 1 mol / L hydrochloric acid is added, and cross-linked starch is obtained by filtering, washing, drying, and crushing;

[0045] Step (2): adding water to the cross-linked starch obtained in step (1) to prepare a solution with a mass concentration of 20%, then adding 1 kg of phosphate buffer, and stirring in a 60° C. water bath for 20 minutes to obtain a mixed emulsion;

[0046] Step (3): dissolving 0.2 kg of complex enzyme in 0.5 kg of phosphate buffer into enzyme solution and then slowly adding it into the mixed emulsion, reacting for 5 hours and centrifuging, washing the obtained solid with water and drying it, and then obtaining the cross-linked microporous starch.

[0047] Preparation Example 2-3

[0048] The difference between Preparation Example 2-3 and the above Preparation Example 1 lies in: the difference in material type and amount, and the difference in process conditions, see Table 2 below for details.

[0049] Table 2 Material types, dosage and process of preparation examples 1-3

[0050]

[0051]

[0052] Preparation Comparative Example 1

[0053] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the corn starch in Preparation Example 1 is replaced with an equal amount of tapioca starch.

[0054] Preparation Example Comparative Example 2

[0055] The difference between Preparation Comparative Example 2 and Preparation Example 1 is that in step (3) of Preparation Example 1, phosphate buffer solution is not used to dissolve the complex enzyme, but the complex enzyme is directly heated in the mixed solution.

[0056] Example

[0057] Example 1

[0058] A method for preparing a degradable blister box comprises the following steps:

[0059] 1. Step A: 0.75 kg of L-polylactic acid, 0.27 kg of D-polylactic acid, 0.1 kg of glass fiber, 0.1 kg of diatomaceous earth, 0.3 kg of cross-linked microporous starch, 0.05 kg of phosphite, 0.15 kg of thiobisphenol, 0.1 kg of sorbitol and 0.3 kg of polycarbodiimide were added into a rubber mixer, heated at 190° C. and mixed for 20 min to obtain a mixture;

[0060] Step B: Extruding the mixture obtained in step A through an extruder at a pressure of 20 MPa to obtain a sheet;

[0061] Step C: The sheet obtained in step B is heated to 150° C. and then formed by vacuum suction. After cooling, the sheet is cut to obtain a degradable blister box.

[0062] Embodiment 2-5

[0063] The difference between Examples 2-5 and Example 1 is that the amount, type and process of raw materials are different, see Table 3 below for details.

[0064] Table 3 Amount, type and process of raw materials in Examples 1-5

[0065]

[0066]

[0067] Example 6

[0068] The difference between Example 6 and Example 1 is that the equal amount of L-polylactic acid in Example 1 is replaced by the equal amount of D-polylactic acid.

[0069] Example 7

[0070] The difference between Example 7 and Example 1 is that the equal amount of dextrorotatory polylactic acid in Example 1 is replaced by the equal amount of l-rotatory polylactic acid.

[0071] Comparative Example

[0072] Comparative Example 1

[0073] The difference between Comparative Example 1 and Example 1 is that the polylactic acid in Example 1 is replaced by an equal amount of polyethylene resin.

[0074] Comparative Example 2

[0075] The difference between Comparative Example 2 and Example 1 is that no glass fiber is added in Example 1.

[0076] Comparative Example 3

[0077] The difference between Comparative Example 3 and Example 1 is that diatomaceous earth is not added in Example 1.

[0078] Comparative Example 4

[0079] The difference between Comparative Example 4 and Example 1 is that cross-linked microporous starch is not added in Example 1.

[0080] Comparative Example 5

[0081] The difference between Comparative Example 5 and Example 1 is that the cross-linked microporous starch in Example 1 is replaced by an equal amount of corn starch.

[0082] Comparative Example 6

[0083] The difference between Comparative Example 6 and Example 1 is that no inorganic filler is added in Example 1.

[0084] Performance testing

[0085] The degradable blister boxes prepared according to the above-mentioned Examples 1-7 and Comparative Examples 1-6 were subjected to compressive strength test, tensile strength test, water absorption test, Vicat softening temperature test, and degradation performance test, and the test results are shown in the table below. The compressive strength test was measured with reference to the standard "GB / T1041-1992 Plastic Compression Performance Test Method"; the tensile strength test was measured with reference to the standard "GB / T1040-1992 Plastic Compression Performance Test Method"; the water absorption test was measured with reference to the standard "GB / T1034-1998 Plastic Water Absorption Test Method"; the Vicat softening temperature test was measured with reference to the standard "GT / B1633-20000 Determination of Vicat Softening Temperature of Thermoplastic Plastics".

[0086] The test results of compressive strength test, tensile strength test and Vicat softening temperature test are shown in Table 4 below.

[0087] Table 4 Compressive strength, tensile strength, Vicat softening temperature test results

[0088]

[0089]

[0090] Referring to Table 4 in combination with Examples 1-7, it can be seen that the biodegradable blister box of the present application has good compressive strength, tensile strength and Vicat softening temperature. It is not easy to soften when containing high-temperature soup or hot drinks, and is not easily squeezed and deformed during transportation. Compared with Example 1, the compressive strength, tensile strength and Vicat softening temperature of Comparative Example 1 are all reduced, indicating that the performance of the blister box prepared using polylactic acid is relatively good, the strength is high, and it is not easy to soften when heated; the strength and Vicat softening temperature of Comparative Example 2 are both reduced a lot. The reason is that the glass fiber has excellent heat insulation and heat resistance, which can enhance the strength of the blister box. The Vicat softening temperatures of Comparative Examples 3, 4 and 5 are significantly reduced, indicating that diatomaceous earth and cross-linked microporous starch can enhance the heat resistance of the blister box. The reason is that diatomaceous earth and cross-linked microporous starch both have a network-like microporous structure, and this structure has good heat resistance.

[0091] Degradation performance test

[0092] The boxes and thermal insulation films prepared in Example 1 and Comparative Examples 1-6 were buried in the soil respectively, and observed every ten days to calculate the weight loss rate (weight loss rate = [(original mass - remaining mass) / original mass] * 100%). The results are shown in Table 5 below.

[0093] Table 5 Degradability test results

[0094]

[0095]

[0096] Referring to Table 5, it can be seen that the blister box of the present application has excellent degradability, fast degradation speed and high degradation rate. The reason for the low degradation rate of comparative example 1 is that the polyethylene resin does not have biodegradability. The degradation rate of comparative example 5 is 65.3% after 60 days of degradation, which is significantly lower than that of Example 1. The reason is that the degradation rate of corn starch is not as fast as the degradation rate of cross-linked microporous starch.

[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A degradable blister box, characterized in that: The invention comprises the following raw materials in parts by weight: 10-60 parts of polylactic acid, 2-10 parts of antioxidant, 1-8 parts of chain extender, 3-9 parts of hydrolysis resistance agent, 1-8 parts of glass fiber, 1-10 parts of diatomaceous earth, and 3-12 parts of cross-linked microporous starch; The polylactic acid is a mixture of left-handed polylactic acid and right-handed polylactic acid, and the mixing ratio of the left-handed polylactic acid to the right-handed polylactic acid is (6-9):1; The cross-linked microporous starch is prepared by the following steps: Step (1): 20-50 parts of corn starch are ball-milled and mixed with 30-60 parts of water, added into a reaction container, stirred, and preheated at 40-45° C. for 20-30 minutes, and then 1-2.5 parts of sodium chloride solution and 2-8 parts of epichlorohydrin are slowly added to obtain a starch emulsion, and then 3-4 parts of 1 mol / L sodium hydroxide solution are added, reacted for 3-4 hours, and then 2-5 parts of 1 mol / L hydrochloric acid are added, and the cross-linked starch is obtained by filtering, washing, drying, and crushing; Step (2): adding water to the cross-linked starch obtained in step (1) to prepare a solution with a mass concentration of 20-30%, then adding 10-15 parts of phosphate buffer, heating in a water bath at 60-65° C. and stirring for 20-50 minutes to obtain a mixed emulsion; Step (3): dissolving 2-5 parts of the complex enzyme with 5-10 parts of phosphate buffer into an enzyme solution and then slowly adding the solution to the mixed emulsion, reacting for 5-10 hours and then centrifuging, washing the obtained solid with water and drying, thereby obtaining the cross-linked microporous starch; The complex enzyme is a compound of saccharifying enzyme and α-amylase in a mass ratio of (2-3):

1.

2. The method for preparing a degradable blister box according to claim 1, comprising the following steps: Step A: adding 10-60 parts of polylactic acid, 1-8 parts of glass fiber, 1-10 parts of diatomaceous earth, 3-12 parts of cross-linked microporous starch, 2-10 parts of antioxidant, 1-8 parts of chain extender, and 3-9 parts of hydrolysis resistance agent into a rubber mixer for mixing to obtain a mixture; Step B: Extruding the mixture obtained in step A to obtain a sheet; Step C: The sheet obtained in step B is heated at high temperature and then formed by vacuum suction, and then cooled and cut to obtain a degradable blister box.

3. The method for preparing a degradable blister box according to claim 2, characterized in that: In step A, the mixing temperature is 190° C.-200° C., the stirring speed of the rubber mixer is 40-60 r / min, and the mixing time is 20-30 min.

4. The method for preparing a degradable blister box according to claim 2, characterized in that: The heating temperature of the sheet in step C is 150°C-170°C.

5. The method for preparing a degradable blister box according to claim 4, characterized in that: The chain extender is one of sorbitol and polyhydroxyalkanoate or a combination of the two.

6. The method for preparing a degradable blister box according to claim 4, characterized in that: The antioxidant is a combination of phosphite and thiobisphenol.

7. The method for preparing a degradable blister box according to claim 4, characterized in that: The anti-hydrolysis agent is one or a combination of polycarbodiimide and carbodiimide.

Citation Information

Patent Citations

  • Biodegradable high-temperature-resistant disposable meal box

    CN112876823A

  • Polylactic acid heat-resistant meal box capable of being formed at high speed and preparation method thereof

    CN114656764A